Muhammadiyah’s Advocacy: Empowerment and Policy Protection for Indonesian Migrant Workers in Taiwan - Kurniawan, Bachtiar Dwi; Swarga, Alim Bubu (Analisa: Journal of Social Science and Religion, 2025)
This article explores how Muhammadiyah’s leadership, through its overseas branches, advocates for and empowers Indonesian migrant workers in Taiwan. Grounded in the empowerment framework developed by Laverack and Labonté, the study investigates how faith-based civil society engagement can offer protection and capacity-building for vulnerable migrant populations. Employing a qualitative case study approach, data were collected through semi-structured interviews with key organizational leaders and members, a multi-country focus group discussion involving Indonesian migrant workers, analysis of internal documents, and online observation of program implementation between February 2023 and July 2023. The findings reveal that Muhammadiyah’s initiatives encompass three interrelated domains—legal assistance, economic empowerment, and spiritual reinforcement—implemented through programs such as legal aid clinics, vocational and religious education, financial literacy training, and cross-border advocacy networks. These efforts have helped workers navigate legal uncertainty, secure basic rights, and build collective resilience. Yet, limitations persist, particularly due to Muhammadiyah’s status as a non-state actor without formal authority over migrant affairs, leading to bureaucratic barriers with official institutions, alongside persistent challenges in coordination, volunteer continuity, and sustaining attention and funding through uncertain donation-based resources. This study concludes that Muhammadiyah represents a promising model of transnational Islamic advocacy that integrates moral, social, and institutional elements to support the empowerment of migrant communities navigating complex legal and institutional environments abroad.